The influence of international coffee prices, rupiah exchange rates, and competitor commodity prices (cocoa), on Indonesian coffee exports for the 2003-2022 period - Boy Uli Kirana Situmorang; Isnaini Harahap; Muhammad Ikhsan Harahap (Institute of Computer Science (IOCS), 2023)
Indonesia is a country with potential subtropical areas for the development of primary plantation commodities. One of Indonesia's main plantation commodities is coffee. This study aims to determine the effect of International Coffee Prices (x1), Rupiah Exchange Rates (x2), Competitor Commodity Prices (cocoa) (x3) on the value of Indonesian coffee exports (Y).In this study using quantitative descriptive analysis with the type of time series data in which the data is arranged in a time series.The results showed that the Rupiah Exchange Rate had a significant effect on Coffee Exports in Indonesia in 2003 – 2022. The acquisition of the Rupiah exchange rate benefited the economy because according to the theory the price of goods in the country was cheaper when compared to prices in other countries. This condition causes coffee exports to increase. International coffee prices have a significant effect on coffee exports in Indonesia in 2003 - 2022. Furthermore, competing commodity prices (cocoa) have no effect on coffee exports in Indonesia in 2003-2022 and together international coffee prices, the rupiah exchange rate and commodity prices Competitors have a significant effect on coffee exports in Indonesia in 2003-2022